Porphyrins bearing a consolidated anthryl donor with dual functions for efficient dye-sensitized solar cells. Issue 1 (16th November 2015) - Wang, Chin-Li; Zhang, Min; Hsiao, Yu-Hsin; Tseng, Chuan-Kai; Liu, Chia-Lin; Xu, Mingfei; Wang, Peng; Lin, Ching-Yao
Abstract : Efficient DSSC performance was achieved by using a porphyrin dye bearing a consolidated anthryl donor which provides both electron-donating and absorption-broadening effects. Abstract : Three porphyrin dyes with different electron-donating groups were prepared to compare their photovoltaic performance in dye-sensitized solar cells. LWP12 is based on LD31 which has a complicated, piece-together electron-donating group, whereas LWP13 and LWP14 have merged substituents with electron-donating and absorption-broadening abilities. The results in this work suggest that consolidated anthryl donors may be used to design highly efficient photosensitizers.